The relationship between human resource management and organizational commitment in Hotel Industry - Law, Cindy Sing Ling (Universiti Malaysia Sarawak, 2003)
This survey studies the relationship between selected human resource management practices (leadership, motivation, training) with organizational commitment, and the comparison of organizational commitment levels according to selected demographic characteristic (marital status, shifts, departments, seniority) in the hotel industry. The scope of the study involves inter- and intra vertical comparison between 3-star, 4-star and 5-star hotels in Kuching